2020
DOI: 10.1097/md.0000000000022333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rational emotive behavioral therapy on personal value system of students with visual impairment

Abstract: Background: Visually impaired students have been reported to struggle with value system and rash decision making process. This study examined the impact of rational emotive behavioral therapy (REBT) in reducing negative personal value system of visually impaired people. Method: A group-randomized trial design was adopted using 56 students with visual impairment. The participants received a value-based rational emotive behavior progamme and were assessed at 3 points usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…To reiterate, previous studies suggested that students with career-related problems can be assisted [38] using rational-emotive techniques to surmount irrational beliefs [39] . In addition, the present study corroborates previous studies that showed the effectiveness of REBT principles and techniques in alleviating the career-related problems, [20,21,40–42] decrease career decision-making anxiety, [28] and change and defeat irrational career beliefs [43,44] . Career education as adopted in this study has been found to be effective in building positive career behaviors and tendencies, thereby enhancing career engagement and development.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To reiterate, previous studies suggested that students with career-related problems can be assisted [38] using rational-emotive techniques to surmount irrational beliefs [39] . In addition, the present study corroborates previous studies that showed the effectiveness of REBT principles and techniques in alleviating the career-related problems, [20,21,40–42] decrease career decision-making anxiety, [28] and change and defeat irrational career beliefs [43,44] . Career education as adopted in this study has been found to be effective in building positive career behaviors and tendencies, thereby enhancing career engagement and development.…”
Section: Discussionsupporting
confidence: 89%
“…Given the growing career indecision and occupational maladjustment which irrational career beliefs have caused in most developing countries, past literature has blamed it on limited psycho-educational interventions that can combat negative ideological beliefs about life including the world of work. [20,21] Hence there is a serious need for researchers in the field of vocation counseling, entrepreneurship, and occupational psychology to engage in research that can promote realistic career beliefs among students in their early careers. [11] Researchers in different studies have explored and recommended reduction of career indecision caused by irrational beliefs and associated negative impacts on carrier paths of individuals using cognitive behavioral approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Other past studies which have also shown the therapeutic benefits of rational emotive behavior interventions in reducing dysfunctional thinking and improving occupational and family health of study participants, [38][39][40][41][42][43][44][45] give credence to our research. To this end, Catholic education authorities could consider using the CRREBT programme to promote WLB among their teaching staff.…”
Section: Discussionmentioning
confidence: 66%
“…In a related study, Malhotra et al (2012) indicated that the existence of a child with disability negatively affects family relationship and wellness. Such negative attitudes and perceptions could be resolved using a well-promising cognitive behavioural treatment (Abiogu et al, 2020a(Abiogu et al, , 2020bAgah et 2020;Agah et al, 2021;Ugwuanyi, et al, 2020aUgwuanyi, et al, , 2020bUgwuanyi, et al, , 2020c like family health-model of REBT among family members to enable them to live up to expectation.…”
Section: Discussionmentioning
confidence: 99%